E-Government in The Implementation of T-Tax System in Palembang City - Eko Aryansyah, Januar; Lionardo, Andries; Budiyanto, M. Nur; Putra, Raniasa (Iapa Proceedings Conference, 2023)
Electronic Government, an essential aspect of contemporary governance, harnesses information technology and the internet to optimize governmental activities, fostering enhanced public services and heightened government efficiency and transparency. This research investigates Palembang City's foray into e-government, specifically in regional tax collection, utilizing an online tax application initiated in 2018. Employing a descriptive qualitative research methodology encompassing interviews, observation, documentation, and literature review, the research reveals Palembang City's strategic move to simplify local tax collection through online taxes. Third-party service providers, in collaboration with Bank Sumsel Babel, play a pivotal role in monitoring and facilitating e-tax implementation. Success factors include robust policy support via Mayor Regulations, alongside effective communication strategies utilizing social and electronic media. Challenges persist, such as uneven distribution of tax payment kiosks and low taxpayer compliance with voluntary e-tax adoption. This research offers comprehensive insights into the complexities and opportunities of regional e-government, illuminating the nuanced landscape of digital governance at the local level.